The Heart of the New Thought - Wilcox, Ella Wheeler, 1850-1919 (Salt Lake City, UT : Project Gutenberg, 2009)
"The Heart of the New Thought" by Ella Wheeler Wilcox is a philosophical book written in the early 20th century. As an exploration of New Thought principles, this work emphasizes the transformative power of right thinking and optimistic belief. It seeks to guide readers toward personal empowerment, encouraging them to change their lives by altering their thoughts and embracing a mindset focused on health, happiness, and success. The content of the book is organized into various thematic sections that address aspects of personal development, such as the importance of letting go of the past, the role of positive thinking, and the significance of self-conquest. Wilcox shares insights on how one's thoughts can shape their reality, illustrating how optimism, generosity, and self-discipline contribute to a fulfilling life. The chapters are filled with practical advice and uplifting perspectives, inviting readers to cultivate a mindset of abundance and strength while navigating the challenges of life. Overall, the book serves as both a motivational guide and a reflection on the philosophy of personal agency and spiritual growth. (This is an automatically generated summary.)
Release date is 2009-10-14
Produced by Al Haines
Keywords: New Thought